2023
DOI: 10.1021/acssuschemeng.2c06738
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Ion Conductivity Epitaxial Layer Contributing to the Structure and Cycling Stability of LiMn2O4 Cathodes

Abstract: A critical challenge in the commercialization of spinel lithium manganate materials is the bulk structure damage and capacity degradation due to manganese dissolution during battery operation. Hence, Li 3 PO 4 with good ionic conductivity was homogeneously deposited on the surface of spinel lithium manganate by the sol−gel method, aiming to improve the stability and cycling of the spinel structure by an epitaxial layer. The structural and electrochemical characterizations reveal that the presence of the Li 3 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…The thin, uniform, and flat carbon layer would be more conducive to the migration of K + and effectively alleviate the huge volume expansion of RP in the process of repeated potassiation/depotassiation, so as to improve the cycle stability of the battery. 22,23 1l,n, S3c and S4c, insets), which is in concordance with the XRD results that the composites are amorphous. In conclusion, the TEM and EDS elemental mapping analyses demonstrated that MPc anchored on RP successfully induced a uniform distribution of the carbon layer on the RP surface, which effectively addressed the issue of incomplete encapsulation of RP by the carbon layer.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The thin, uniform, and flat carbon layer would be more conducive to the migration of K + and effectively alleviate the huge volume expansion of RP in the process of repeated potassiation/depotassiation, so as to improve the cycle stability of the battery. 22,23 1l,n, S3c and S4c, insets), which is in concordance with the XRD results that the composites are amorphous. In conclusion, the TEM and EDS elemental mapping analyses demonstrated that MPc anchored on RP successfully induced a uniform distribution of the carbon layer on the RP surface, which effectively addressed the issue of incomplete encapsulation of RP by the carbon layer.…”
Section: Resultssupporting
confidence: 90%
“…Nevertheless, in comparison with RP/C, where the carbon layer was agglomerated on the RP surface, the agglomeration of the carbon layer in MPc@RP/C was significantly suppressed. The thin, uniform, and flat carbon layer would be more conducive to the migration of K + and effectively alleviate the huge volume expansion of RP in the process of repeated potassiation / depotassiation, so as to improve the cycle stability of the battery. , The selected area electron diffraction (SAED) of particles for the composites shows what are typical amorphous halos (Figures l,n, S3c and S4c, insets), which is in concordance with the XRD results that the composites are amorphous. In conclusion, the TEM and EDS elemental mapping analyses demonstrated that MPc anchored on RP successfully induced a uniform distribution of the carbon layer on the RP surface, which effectively addressed the issue of incomplete encapsulation of RP by the carbon layer.…”
Section: Resultsmentioning
confidence: 99%
“…[69,146,147] Peng et al [148] discovered that the S-LMO possesses a highly ordered structural domain with lattice fringe spacing of 0.47 nanometers, which related to the (003) crystallographic planes of the LMO. [149] They also found that the spent cathode had distinct disordered regions, amorphous phases, and corrosion holes in addition to the structure of the spinel LMO (Figure 10d,e). During the cycling process, these undesirable phases, which exhibit no electrochemical activity, cause a diminishment of capacity and an increasement in impedance.…”
Section: Degradation Mechanisms Of Lmo and The Corresponding Characte...mentioning
confidence: 92%